2020
DOI: 10.1186/s40066-020-00268-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and environmental factors influence the proximate composition and quality attributes of sweetpotato (Ipomoea batatas L.)

Abstract: Background Sweetpotato is an important staple food crop worldwide. The genotype mainly influences the nutritional quality of its storage roots, but environmental conditions could produce significant variations in chemical composition and quality. The aim of this study was to characterize sweetpotato diversity of 20 selected genotypes and identify harvest time (90, 120, and 150 days after planting-DAP) and environmental effects on quality attributes estimated by proximate analysis (dry matter, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The breakdown of starch into sugars might have resulted in the increase in total sugar content, which is directly responsible for the increase of TSS during storage. Similar results were obtained by Thriveni et al( 2019) and Rosero et al (2020), who observed that moisture reduction resulted in the increase of total sugar content, which is directly responsible for high TSS during storage.…”
Section: Total Soluble Solids (%)supporting
confidence: 90%
“…The breakdown of starch into sugars might have resulted in the increase in total sugar content, which is directly responsible for the increase of TSS during storage. Similar results were obtained by Thriveni et al( 2019) and Rosero et al (2020), who observed that moisture reduction resulted in the increase of total sugar content, which is directly responsible for high TSS during storage.…”
Section: Total Soluble Solids (%)supporting
confidence: 90%
“…They reported that the genotypic factor significantly affected the dry matter composition of Guinea yam. Variations in the biochemical components of white yam may be caused by environmental factors in the growing area, such as the climate and soil nutrients ( Rosero et al., 2020 ). The analysis of variance for the biochemical composition also shows that both clones and location showed a highly significant effect (p ≤ 0.001) on the biochemical composition except ash content which is slightly significant at p ≤ 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported in fertilizer applications in various studies ( 70 72 ). The abundance of organic matter and micronutrients in soils positively influenced a higher accumulation of proximate nutrients, and the higher nutrient availability in soils promoted better nutritional quality in storage roots ( 73 ). The optimal level of nutrient in fertilizers enhances the accumulation of nutrients in different parts of a plant ( 74 ).…”
Section: Discussionmentioning
confidence: 99%